2016
DOI: 10.1111/ijfs.13312
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the role of microorganisms in water kefir fermentations

Abstract: Water kefir is a slightly alcoholic, lactic and acetic beverage fermented by yeasts, lactic acid bacteria and acetic acid bacteria that are associated with the polysaccharide of the water kefir grains. In this study, the three main metabolic products of microorganisms were evaluated during a traditional 192-h water kefir fermentation and also after inoculating the microorganisms in fresh medium or sterilised broth from different fermentation stages. The first process to occur was alcoholic fermentation, carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 50 publications
3
28
0
Order By: Relevance
“…In contrast to milk kefir, there is only very limited research on water kefir. Most of the available studies focused on its species diversity ( Ward, 1891 ; Pidoux, 1989 ; Neve and Heller, 2002 ; Gulitz et al, 2011 ; Marsh et al, 2013 ; Laureys and De Vuyst, 2014 ; Martínez-Torres et al, 2017 ), or on the chemical and structural composition of the water kefir grains ( Horisberger, 1969 ; Pidoux et al, 1988 ; Pidoux et al, 1990 ; Waldherr et al, 2010 ; Fels et al, 2018 ; Xu et al, 2018 ). To date, several attempts have been made to understand the interactions of the microorganisms in water kefir.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to milk kefir, there is only very limited research on water kefir. Most of the available studies focused on its species diversity ( Ward, 1891 ; Pidoux, 1989 ; Neve and Heller, 2002 ; Gulitz et al, 2011 ; Marsh et al, 2013 ; Laureys and De Vuyst, 2014 ; Martínez-Torres et al, 2017 ), or on the chemical and structural composition of the water kefir grains ( Horisberger, 1969 ; Pidoux et al, 1988 ; Pidoux et al, 1990 ; Waldherr et al, 2010 ; Fels et al, 2018 ; Xu et al, 2018 ). To date, several attempts have been made to understand the interactions of the microorganisms in water kefir.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of oxygen allowed the proliferation of AAB, resulting in high concentrations of acetic acid ( Laureys et al, 2018 ). In addition, three main metabolic products were evaluated from the carbon flux from sucrose during 192 h of fermentation ( Martínez-Torres et al, 2017 ). After 24 h, lactic and acetic acid have been postulated to be initially produced by L. hilgardii and subsequently produced by Acetobacter spp., mainly A. tropicalis .…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, our results show a final pH consistent with the lowest acidification power of yeast versus lactic acid bacteria. 20 Moreover, H. opuntiae population decreased significantly after 3 days ( Fig. 1), due to acid accumulation and decrease of pH in the Guajillo sauce.…”
Section: Resultsmentioning
confidence: 95%
“…The starter cultures used in the fermentation are grains composed of water and polysaccharides and different microorganisms. Martínez-Torres, et al [64] found the occurrence of S. cerevisiae (responsible for alcoholic fermentation) in the early stage of the process and other yeasts as Candida californica and Pichia membranefaciens.…”
Section: Yeasts As Probiotics/symbiotics In Low/non-alcoholic Drinksmentioning
confidence: 99%